Miniaturized broadband metasurface antenna using stepped impedance resonators - Wei Liu; Zhi Ning Chen; Xianming Qing (2016 IEEE 5th Asia-Pacific Conference on Antennas and Propagation (APCAP), 2016)
A miniaturized low-profile broadband metasurface antenna by using stepped impedance resonators (SIRs) is presented. H-shaped SIR elements are employed in the proposed aperture coupled metasurface antenna. The exemplified SIR metasurface antenna with a footprint of 11.8mm × 11.0mm × 1.524mm (0.40λ 0 × 0.37λ 0 × 0.05λ 0 at the center frequency of 10.1 GHz) shows the operating frequencies over the range of 9.43-10.77 GHz and gain ranging from 6.1 dBi to 7.8 dBi.